Lithium-ion batteries and electronic devices
By using high -content SI systems and specific electrolyte components in lithium -ion batteries, the capacity attenuation and battery inflation caused by SI -based materials in the cycle are solved, and higher energy density and better battery performance are achieved.
Patent Information
- Application Number
- CN202411365566.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-29
AI Technical Summary
During the circulation process, existing lithium-ion batteries have excessive capacity decayed too fast and the cell thickness expanded too much, which limits the increase in energy density.
The lithium ion battery with a high -content SI system is used to form a coagulative electrolyte to inhibit the expansion of the SI particles and the destruction of the SEI membrane by adding fluoroser carbonate and acrylic compounds to the electrolyte to inhibit the expansion of the SI particles.
The volume expansion and capacity maintenance rate of SI particles are effectively suppressed, the energy density of the battery is improved, and the capacity maintenance rate and safety performance of the battery cycle are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a lithium-ion battery and an electronic device. Background Art
[0002] Lithium-ion batteries are widely used in 3C digital, power tools, aerospace, energy storage, power vehicles and other fields due to their advantages such as high specific energy, no memory effect and long cycle life. In particular, the 3C field has higher requirements on energy density.
[0003] At present, for lithium-ion batteries with lithium cobalt oxide and nickel-cobalt-manganese ternary material systems, one direction to improve energy density is to increase the gram capacity of negative electrode active materials, such as mixing Si-based negative electrode materials into graphite to improve energy density. However, since the volume of Si-based negative electrode materials expands by nearly 300% after lithiation, the particles rupture and expose a larger negative electrode active area after rupture, and then the side reaction with the electrolyte is too intense, causing the battery capacity to decay too quickly during the cycle. These undesirable phenomena greatly restrict the mixing of high-content Si-based materials into negative electrode materials to improve battery energy density.
[0004] Therefore, how to solve the problem of rapid capacity decay and excessive expansion of battery cell thickness during the cycle of lithium-ion batteries with a high content of silicon-based materials, so as to meet users' requirements for high energy density of batteries. Summary of the invention
[0005] In order to solve or partially solve the problems existing in the related art, the present application provides a lithium-ion battery and an electronic device, which can improve the battery energy density through a high-content Si system while ensuring the battery capacity retention rate and controlling the volume expansion rate during the cycle process, thereby meeting the battery safety performance.
[0006] In a first aspect, the present application provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and a condensed electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on the surface of the negative electrode current collector; wherein the negative electrode active material of the negative electrode material layer comprises a silicon-based material;
[0007] The raw materials of the electrolyte include solvent, additive, lithium salt, monomer and initiator; wherein the additive includes fluoroethylene carbonate, and the monomer includes acrylate compound.
[0008] In some embodiments, the mass ratio of the acrylic acid ester compound to the fluoroethylene carbonate is 0.029 to 0.6.
[0009] In some embodiments, the acrylate compound contains at least 2 acrylate groups or at least 2 methacrylate groups.
[0010] In some embodiments, the mass percentage of the monomer in the electrolyte is 1% to 10%.
[0011] In some embodiments, the mass percentage of the monomer in the electrolyte is 1% to 5%.
[0012] In some embodiments, the content of the silicon-based material in the negative electrode active material is a% by mass, the content of the fluoroethylene carbonate in the electrolyte is b% by mass, and the content of the acrylate compound in the electrolyte is c% by mass, wherein b=a*0.5+9.5±m, and / or c= a*0.3+0.7±n; wherein m is selected from 0~2; n is selected from 0~3; a>0, c>0.
[0013] In some embodiments, the initiator is selected from at least one of an azo initiator and a peroxide.
[0014] In some embodiments, the content of the initiator is 1% to 5% by weight of the monomer.
[0015] In some embodiments, the initiator is selected from at least one of azobisisobutylnitrile initiator, azobisisoheptylnitrile, benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, diisopropyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, potassium sulfate, sodium persulfate, and ammonium persulfate.
[0016] In some embodiments, the silicon-based material is selected from at least one of SiO and SiC.
[0017] In some embodiments, the silicon-based material accounts for 3% to 30% by mass of the negative electrode active material.
[0018] In some embodiments, the additive further comprises a polynitrile compound, and the polynitrile compound is selected from at least one of a dinitrile compound, a trinitrile compound, and a tetranitrile compound.
[0019] In some embodiments, the content of the polynitrile compound in the electrolyte is 1% to 10% by weight.
[0020] In some embodiments, the polynitrile compound is selected from at least one of succinonitrile, glutaronitrile, adiponitrile, trans-butenedinitrile, trans-hexenedinitrile, 1,3,6-hexanetricarboxylic acid nitrile, ethylene glycol bis(propionitrile) ether, 1,3,4,6-hexanetetranitrile, 1,2,4,5-benzenetetranitrile, 2,3,5,6-pyrazinetetranitrile, and ethertetranitrile.
[0021] In some embodiments, the solvent is selected from at least two of ethylene carbonate, propylene carbonate, ethyl propionate, propyl propionate, ethyl methyl carbonate, diethyl carbonate, ethyl fluoroacetate, and dimethyl carbonate.
[0022] In some embodiments, the lithium salt is selected from at least one of LiPF6 and F2LiNO4S2, and the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.5 mol / L.
[0023] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on the surface of the positive electrode current collector, and the positive electrode material layer contains a positive electrode active material; wherein: the positive electrode active material is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, nickel cobalt aluminum, and lithium-rich manganese-based.
[0024] A second aspect of the present application provides an electronic device comprising the above-mentioned lithium-ion battery.
[0025] The technical solution provided by this application may have the following beneficial effects:
[0026] The lithium-ion battery of the present application, when a high content of silicon is added to the negative electrode active material, can effectively suppress the expansion of Si particles and the insufficient capacity retention rate by using the above-mentioned electrolyte in the lithium-ion battery, so that the lithium-ion battery has a higher energy density while comprehensively improving the excellent electrical properties including the battery's first efficiency, capacity retention rate during the cycle, volume expansion, and better safety performance in coping with overcharging, puncture, extrusion, and falling.
[0027] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION
[0028] To make the present invention easy to understand, the present invention will be described in detail below. However, before describing the present invention in detail, it should be understood that the present invention is not limited to the specific embodiments described. It should also be understood that the terms used herein are only for describing specific embodiments and are not intended to be limiting.
[0029] Where a numerical range is provided, it is understood that each intervening value between the upper and lower limits of the range and any other specified or intervening values in the specified range is encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges and are also encompassed within the present invention, subject to any explicitly excluded limits in the specified ranges. Where a specified range includes one or two limits, ranges excluding either or both of those included limits are also encompassed within the present invention.
[0030] Unless otherwise defined, all terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials or equivalent methods and materials described herein can also be used in the practice or testing of the present invention, preferred methods and materials are now described.
[0031] In the related art, Si-based materials are added to the negative electrode active materials of lithium-ion batteries to improve the energy density of the battery. Since the volume expansion of Si-based materials is close to 300% after lithiation, the capacity decays too quickly and the thickness of the battery cell expands too much during the cycle, which limits the content of Si-based materials mixed in the negative electrode materials, and then limits the effect of improving the energy density of the battery.
[0032] Based on this, the present application provides a lithium-ion battery that can improve the battery energy density through a high-content Si system while ensuring the battery capacity retention rate and controlling the volume expansion rate during the cycle process, thereby meeting the battery safety performance.
[0033] The present application provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and a condensed electrolyte. The separator is arranged between the positive electrode sheet and the negative electrode sheet. The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer arranged on the surface of the negative electrode current collector.
[0034] Furthermore, the negative electrode material layer contains negative electrode active materials, and the negative electrode active materials contain silicon-based materials. In some embodiments, the silicon-based material can be selected from a mixture of at least one or more of SiO and SiC. By adding silicon-based materials to the negative electrode active materials, the gram capacity of the negative electrode active materials is increased, and then the energy density of the battery can be increased. In some embodiments, the mass proportion of silicon-based materials in the negative electrode active materials is 3% to 30%. For example, the mass proportion of silicon-based materials in the negative electrode active materials is 3%, 5%, 10%, 15%, 25%, 30%, or a value between any two of the above values, which is only exemplified here and is not limited. The negative electrode material layer may also include conductive agents, binders, solvents and other materials, which can be selected according to relevant technologies and are not limited here. In addition, the negative electrode sheet of the present application can be prepared according to relevant technologies, which will not be repeated here.
[0035] Furthermore, the raw materials of the electrolyte of the present application include solvents, additives, lithium salts, monomers and initiators; wherein the additives include fluoroethylene carbonate (FEC), and the monomers include acrylate compounds. The monomers are polymerized by the initiator to form a condensed electrolyte. Further, in the electrolyte of the present application, FEC can promote the formation of SEI film on the negative electrode active material. However, due to the general mechanical properties of the SEI film formed by silicon particles, the expansion of silicon-based materials and the continuous destruction of SEI cannot be suppressed. By using acrylate monomers to polymerize to generate a condensed electrolyte, which is equivalent to a semi-solid electrolyte, a high mechanical strength package can be formed on the surface of silicon particles. In this way, on the one hand, the volume expansion, pulverization, and disconnection of the conductive path of silicon particles can be suppressed, and the side reactions at the interface between silicon particles and the electrolyte are reduced, and the transition growth of the SEI film and its consumption of active lithium are suppressed, thereby improving the capacity retention rate of the battery and extending the service life of the battery. Even if a small amount of Si interface is broken, FEC can be restored and repaired in time, forming a good protection for the negative electrode interface, thereby exerting the synergistic effect of FEC and the semi-solid electrolyte. On the other hand, the high adhesion of the gel-state polymer enhances the adhesion between the electrode and the diaphragm, significantly reducing the growth of the interface contact impedance. In addition, the semi-solid electrolyte forms a uniform coating protection on the surface of the negative electrode and the diaphragm, improving the stability of the SEI film and reducing the thermal failure temperature. The thicker diaphragm coating can reduce the short circuit point and improve the safety performance of the lithium-ion battery in response to needle puncture, extrusion, and falling.
[0036] From this example, it can be seen that when a high content of silicon is added to the negative electrode active material, the expansion of Si particles and the insufficient capacity retention rate can be effectively suppressed by using the above-mentioned electrolyte in the lithium-ion battery, so that the lithium-ion battery has a higher energy density while comprehensively improving the excellent electrical properties including the battery's first efficiency, capacity retention rate during the cycle, volume expansion, and better safety performance in response to overcharging, puncture, extrusion, and falling.
[0037] In some embodiments, the acrylate compound contains at least two acrylate groups or methacrylate groups. The structural formulas of acrylate groups and methacrylate groups are shown in Table 1 below.
[0038]
[0039] Furthermore, in some embodiments, the monomer of the present application may be at least one of the following acrylate compounds. The structural formula of each monomer is shown in Table 2 below.
[0040]
[0041] It is to be understood that the monomers of the present application may also be other acrylate compounds containing acrylate or methacrylate groups, and the above table is only for illustration and not for limitation.
[0042] Furthermore, in some embodiments, the mass proportion of the monomer in the electrolyte is 1% to 10%; more preferably, the mass proportion of the monomer in the electrolyte is 1% to 5%. For example, the mass proportion of the monomer can be 1%, 2%, 3%, 5%, 8%, 10%, or a value between any two of the above values, which is only for illustration and not for limitation.
[0043] In some embodiments, the mass ratio of the acrylate compound to the fluoroethylene carbonate is 0.029 to 0.6. By limiting the content of the acrylate compound to the fluoroethylene carbonate, the two can achieve a better synergistic effect.
[0044] In some specific embodiments, the mass percentage of the silicon-based material in the negative electrode active material is a%, the mass percentage of the fluoroethylene carbonate in the electrolyte is b%, and the mass percentage of the acrylate compound in the electrolyte is c%, wherein b=a*0.5+9.5±m, and / or c=a*0.3+0.7±n; wherein m is selected from 0 to 2; n is selected from 0 to 3; a>0, c>0. That is, at least one of the above formulas b and c is met, or both are met.
[0045] In a high-content silicon system, the FEC content is positively correlated with the Si content; the acrylate polymer is positively correlated with the Si content. The main function of FEC is to form a film of the negative electrode active material, but the mechanical properties of the corresponding SEI film are poor; after the acrylate monomer is polymerized, a condensed electrolyte is generated, which forms a high mechanical strength package on the surface of the Si particles, which can inhibit the volume expansion, pulverization, and disconnection of the conductive path of the Si particles, and also reduce the side reactions at the interface between the Si particles and the electrolyte, and inhibit the transition growth of the SEI film and its consumption of active lithium; at the same time, the high adhesion of the gel-state polymer enhances the adhesion between the electrode and the diaphragm, and significantly reduces the growth of the interface contact impedance. In addition, the semi-solid electrolyte forms a uniform coating protection on the surface of the negative electrode and the diaphragm, which improves the stability of the SEI film, reduces the thermal failure temperature, and the thicker diaphragm coating can reduce the short circuit point, improving the safety performance of lithium-ion batteries in response to puncture, extrusion, and falling. In this way, the capacity retention rate and volume expansion rate of high-silicon lithium-ion batteries during the cycle process can be improved, allowing lithium-ion batteries to safely and stably achieve high energy density and reliable service life.
[0046] Furthermore, the content of the initiator is set accordingly according to the content of the monomer. In some embodiments, the content of the initiator is 1% to 5% of the weight of the monomer. For example, the content of the initiator can be 1%, 2.5%, 5% of the weight of the monomer, or a value between any two of the above values, which is only illustrative and not limiting.
[0047] In some embodiments, the initiator is selected from at least one of an azo initiator and a peroxide. In some specific embodiments, the initiator is selected from at least one of azobisisobutylnitrile initiator, azobisisoheptylnitrile, benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, diisopropyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, potassium sulfate, sodium persulfate, and ammonium persulfate. Preferably, the initiator is azobisisobutylnitrile.
[0048] In some embodiments, the solvent in the electrolyte is selected from at least two of ethylene carbonate, propylene carbonate, ethyl propionate, propyl propionate, ethyl methyl carbonate, diethyl carbonate, ethyl fluoroacetate, and dimethyl carbonate.
[0049] In some embodiments, the lithium salt in the electrolyte is selected from at least one of LiPF6 and F2LiNO4S2, and the concentration of the lithium salt in the electrolyte is 0.8mol / L to 1.5mol / L. Preferably, the concentration of the lithium salt in the electrolyte may be 1.08mol / L to 1.2mol / L. For example, the concentration of the lithium salt in the electrolyte may be 0.8mol / L, 1.08mol / L, 1.15mol / L, 1.2mol / L, 1.5mol / L, or a value between any two of the above values, which is only illustrative and not limiting.
[0050] In some embodiments, the additive in the electrolyte further includes a polynitrile compound, which is selected from at least one of a dinitrile compound, a trinitrile compound, and a tetranitrile compound. The addition of the polynitrile compound can passivate the positive electrode material and improve the high temperature and safety performance of the battery.
[0051] In some specific embodiments, the polynitrile compound is selected from at least one of succinonitrile, glutaronitrile, adiponitrile, trans-butenedinitrile, trans-hexenedinitrile, 1,3,6-hexanetricarboxylic acid nitrile, ethylene glycol bis(propionitrile) ether, 1,3,4,6-hexanetetranitrile, 1,2,4,5-benzenetetranitrile, 2,3,5,6-pyrazinetetranitrile, and ethertetranitrile.
[0052] Further, in some embodiments, the mass proportion of the polynitrile compound in the electrolyte is 1% to 10%. For example, the content of the polynitrile compound can be 1%, 1.5%, 2%, 3%, 5%, 8%, 9%, 10% of the monomer mass, or a value between any two of the above values, which is only exemplified here without limitation. By adding an appropriate amount of polynitrile compounds, the synergistic effect of FEC, semi-solid electrolyte, and polynitrile additives, on the one hand, strengthens the initial stability of the SEI film, enables the battery to better repair the SEI film during the cycle, and inhibits the expansion of Si particles and their damage to the SEI film and the consumption of active lithium; on the other hand, the polynitrile additive can effectively passivate the high-voltage positive electrode, inhibiting the positive electrode interface side reaction and the rapid decay of the positive electrode structure and the dissolution of transition metals.
[0053] Further, in some embodiments, the positive electrode sheet of the present application includes a positive electrode current collector and a positive electrode material layer disposed on the surface of the positive electrode current collector, and the positive electrode material layer contains a positive electrode active material. The positive electrode current collector can be a conventional metal foil or a composite current collector, which is not limited here.
[0054] In some embodiments, the positive electrode active material is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, nickel cobalt aluminum, and lithium-rich manganese. Preferably, the positive electrode active material can be lithium cobalt oxide. It is understood that the positive electrode material layer can also include materials such as a conductive agent, a binder, and a solvent. These materials can be selected according to relevant technologies and are not limited here. In addition, the positive electrode sheet of the present application can be prepared according to relevant technologies, which will not be repeated here.
[0055] An embodiment of the present application also provides an electronic device, which includes the above-mentioned lithium-ion battery. The lithium-ion battery serves as a power source for the electronic device and can also be used as an energy storage unit for the electronic device. The electronic device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0056] In order to make the present invention easier to understand, the preparation of the lithium ion battery of the present application will be further described in detail below in conjunction with the examples. These examples are only for illustrative purposes and are not limited to the application scope of the present application. The raw materials or components used in the present application can be obtained through commercial channels or conventional methods unless otherwise specified.
[0057] Example 1
[0058] 1) Preparation of positive electrode sheet
[0059] The positive electrode active material LCO (lithium cobalt oxide), the conductive agent CNT (carbon nanotube), and the binder PVDF (polyvinylidene fluoride) are fully stirred and mixed in N-methylpyrrolidone solvent at a mass ratio of 97:1.5:1.5 to form a uniform positive electrode slurry. The positive electrode slurry is applied to the surfaces of both sides of the positive electrode current collector aluminum foil to form a positive electrode material layer. After drying and cold pressing, the positive electrode sheet is obtained.
[0060] 2) Preparation of negative electrode sheet
[0061] The negative electrode active materials silicon carbon and graphite, the conductive agent acetylene black, the binder styrene butadiene rubber and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 14.25:80.75:2:2:1 to form a uniform negative electrode slurry. The negative electrode slurry is coated on both sides of the negative electrode current collector copper foil to form a negative electrode material layer, and then dried and cold pressed to obtain a negative electrode sheet.
[0062] 3) Preparation of electrolyte
[0063] The solvents EC, PC, and PP are mixed in a mass ratio of 15:15:70 to form an organic solvent of 100wt%. According to the percentage of the total weight of the electrolyte, the additive FECPS, at least one polynitrile compound, and an acrylate compound monomer, and an initiator AIBN are added to the organic solvent. After the aforementioned substances are mixed evenly, LiPF6 is added to obtain a mixed solution with a LiPF6 concentration of 1.15mol / L to obtain an electrolyte. In each example, the total content of PS in the electrolyte is 4wt%.
[0064] Note: EC is ethylene carbonate, PC is propylene carbonate, PP is propyl propionate, FEC is fluoroethylene carbonate, PS is 1,3-propylene sultone, HTCN is 1,2,3-hexanetrinitrile, SN is succinonitrile, ADN is adiponitrile, DENE is ethylene glycol bis(propionitrile) ether, and AIBN is azobisisobutyronitrile.
[0065] 4) Preparation of lithium-ion batteries
[0066] The diaphragm in this step is a PE porous polymer film.
[0067] The positive electrode sheet, separator and negative electrode sheet prepared in step 1) are stacked in sequence, and the separator is located between the positive and negative electrode sheets for isolation. The stacked positive electrode sheet, separator and negative electrode sheet are wound into a bare cell. The bare cell is placed in an outer packaging bag, dried at high temperature until the water content of each electrode sheet is less than 100ppm, and then the electrolyte prepared in step 3) is injected at a liquid injection coefficient of 2g / Ah. After vacuum packaging, standing, formation, shaping and other processes, a lithium-ion battery is prepared.
[0068] Among them, the standing stage of the present application is different from the conventional lithium-ion battery preparation process. Specifically, in order to form a condensed electrolyte, in some embodiments, it is first stood for a first period of time at room temperature without pressure, and then stood for a second period of time at high temperature and pressure. In some embodiments, the first period of time can be 10h~72h. The second period of time can be 1h~24h. The pressure range of pressurization can be selected from 0.1 MPa~1 MPa; preferably, it can be 0.3 MPa~0.6 Mpa; the temperature range of high temperature can be 30℃~80℃. For example, it can be stood for 72h at room temperature without pressure, then heated to 60℃ and pressurized to 0.3Mpa for 10h.
[0069] According to the same method as above, lithium ion batteries corresponding to Examples 2 to 34 and Comparative Examples 1 to 5 were prepared respectively. The relevant components of the electrolyte in each Example and Comparative Example are shown in Table 3-1, Table 3-2, Table 4 to Table 5, which will not be repeated here.
[0070]
[0071]
[0072]
[0073]
[0074] Note:
[0075] 1. The blank cells in Table 3-1, Table 3-2, Table 4 and Table 5 above indicate that the substance does not exist in the corresponding examples.
[0076] 2. The percentage of the initiator content in Table 3-1, Table 3-2, Table 4, and Table 5 is the percentage relative to the mass of the monomer. The content of the monomer and each additive in the electrolyte is the percentage relative to the total mass of the electrolyte. The percentage of the silicon content is the percentage relative to the mass of the negative electrode active material.
[0077] The lithium-ion batteries prepared in the above-mentioned Examples 1 to 34 and Comparative Examples 1 to 5 were subjected to the following performance tests.
[0078] (1) 25℃ cycle test
[0079] Test method: Place the battery in an environment of 25±2℃ and perform charge and discharge cycles according to the standards described below. The charge rate is 3C, the discharge rate is 1C, and the charge voltage is 3.0V~4.55V. Calculate the capacity retention rate of the battery after the 300th cycle. The calculation formula is as follows:
[0080] Capacity retention rate at the 300th cycle (%) = (discharge capacity at the 300th cycle) / (discharge capacity at the first cycle)*100%.
[0081] (2) 45℃ cycle test
[0082] Test method: Place the battery in an environment of 45±2℃ and perform charge and discharge cycles according to the standards described below, with a charge rate of 3C, a discharge rate of 1C, and a charge voltage of 3.0V~4.55V. Calculate the capacity retention rate and thickness expansion rate of the battery after the 300th cycle (the thickness test uses a PPG battery thickness gauge, and the weight is set to 700g). The calculation formula is as follows:
[0083] The 300th cycle capacity retention rate (%) = (300th cycle discharge capacity) / (first cycle discharge capacity) * 100%.
[0084] Thickness expansion rate at the 300th cycle (%) = (battery thickness after the 300th cycle) / (battery initial thickness before cycle test) * 100%.
[0085] (3) 45℃ intermittent cycle test
[0086] Test method: Place the battery in an environment of 45±2℃, charge it at a constant current of 1C to 4.55V (charge it at a constant voltage of 0.05C), let it stand at 4.55V for 24 hours, then discharge it at a constant current of 1C to 3.0V, let it stand for 5 minutes, repeat the above charge and discharge process 40 times (voltage window 3.0V~4.55V), and calculate the capacity retention rate of the battery after the cycle. The calculation formula is as follows:
[0087] The 40th cycle capacity retention rate (%) = (40th cycle discharge capacity) / (first cycle discharge capacity) * 100%.
[0088] (4) 45℃ floating charge test
[0089] Test method: Place the battery in a constant temperature box at 45±2℃. At room temperature, charge the battery to 4.55V at 1C constant current (charge to 0.05C at constant voltage), and continue charging at 4.55V for 45D (i.e. 45 days), and record the battery thickness, and calculate the thickness expansion rate of the battery after continuous charging (the thickness test uses a PPG battery thickness gauge, and the weight is set to 700g). The calculation formula is as follows:
[0090] Thickness expansion rate (%) = (battery thickness after continuous charging for 45D - battery initial thickness before test) / (battery initial thickness before test) * 100%.
[0091] (5) Hot box test
[0092] Test method: Place 10 batteries in a high and low temperature box at 25±2℃, and charge the batteries to 4.55V at 1C constant current (charge to 0.05C at constant voltage) at room temperature. After standing for 2 hours, place the batteries in the hot box of the high and low temperature box, heat the hot box to 132℃ at a rate of 5℃ / min within 1 hour, and keep it in the hot box for another 2 hours.
[0093] After the test is completed, record the number of qualified batteries among the 10 batteries. Note: If leakage, fire or combustion occurs, it is judged as unqualified. If none of these occurs, it is judged as qualified.
[0094] (6) Heavy object impact test
[0095] Test method: At room temperature, charge 10 batteries at 0.5C until they are fully charged (constant voltage charging to 4.55V, 0.05C cut-off), and leave them for 2 hours. Place a stainless steel round bar with a diameter of about 15.8±0.2mm on the surface of each fully charged battery perpendicular to the axis, and let a weight of about 9.1±0.1kg fall freely from a height of 610±25mm through the round bar to act on the battery.
[0096] After the test is completed, the battery is left at room temperature for 2 hours. Finally, the number of qualified batteries is recorded. Note: If leakage, fire or combustion occurs, it is judged as unqualified. If none of these situations occurs, it is judged as qualified.
[0097] (7) Acupuncture test
[0098] Test method: At room temperature, charge 10 batteries to 4.55V at 0.5C constant current and constant voltage, and cut off at 0.05C. After standing for 1H, use a nail with a diameter of 2.5mm to completely penetrate the battery at a penetration speed of 100 mm / s.
[0099] After the test, continue to observe the battery for 6 hours. Finally, record the number of qualified batteries among the 10 batteries. Note: If leakage, fire or combustion occurs, it is judged as unqualified. If none of these occurs, it is judged as qualified.
[0100] The test results of the test items corresponding to the lithium-ion batteries of the above examples are shown in the following Tables 6-1, 6-2 and 6-3.
[0101]
[0102]
[0103]
[0104] Test result analysis:
[0105] 1. According to Table 3-1, Table 3-2 and Table 6-1, Table 6-2 and Table 6-3, comparative examples 1 to 5 and embodiments 1 to 15 are compared and analyzed.
[0106] 1. The test results corresponding to Comparative Examples 1 to 4 show that the addition of negative electrode film-forming additive FEC can significantly inhibit the excessive capacity decay and gas production during the cycle process, but when the FEC content is sufficient and continues to increase, the capacity and thickness expansion during the cycle process will no longer improve. The main reason is that the mechanical properties of the SEI film formed by FEC are relatively general, and it can only repair the SEI film on the surface of the negative electrode material layer after the silicon negative electrode expands and ruptures, but it cannot inhibit the silicon expansion and the continuous damage of the SEI film. In addition, when the FEC content is too high, its high temperature performance decreases instead. The main reason is that under high temperature conditions, FEC has poor stability and will decompose and release HF, thereby etching the silicon material and SEI film, which has a negative effect.
[0107] 2. Comparative Example 5 The test results corresponding to Examples 1 to 15 show that after adding an appropriate amount of FEC and further introducing an appropriate amount of acrylate compounds, the high and low temperature cycle capacity retention rate of the battery, the thickness expansion of the battery, and the safety performance are significantly improved. Among them, the improvement of electrical performance is mainly due to the formation of condensed electrolytes after the monomers of the acrylate compounds are polymerized, thereby forming a high mechanical strength package on the surface of the silicon particles. In this way, on the one hand, the volume expansion, pulverization and disconnection risks of silicon particles are suppressed, and the side reactions at the interface between silicon and the electrolyte are also reduced, the transition growth of the SEI film and its consumption of active lithium are suppressed, and then the capacity retention rate during the battery cycle is improved, and the service life of the battery is extended. On the other hand, the high adhesion of the condensed polymer enhances the bonding between the pole piece and the diaphragm, significantly reduces the growth of the interface contact impedance, thereby reducing the polarization phenomenon of the battery, and then improves the capacity retention rate after the battery cycle, and can also improve the thickness expansion rate of the battery. Even if a small amount of silicon film is broken, FEC can restore and repair the interface in time, forming a good protection for the negative electrode interface, thereby exerting the synergistic effect of FEC and semi-solid electrolyte. The improvement in safety performance is mainly due to the fact that the semi-solid electrolyte forms a uniform coating protection on the surface of the negative electrode and the diaphragm. On the one hand, it improves the stability of the SEI film, reduces the thermal failure temperature, and the thicker diaphragm coating reduces the short circuit points. On the other hand, the electrolyte includes gel polymers and liquid organic solvents. The gel polymer wrapping the surface of the electrode can be regarded as acting as an SEI film, thereby isolating side reactions and conducting lithium ions. At the same time, the gel polymer can reduce the contact between the liquid part of the electrolyte and the active material on the electrode, significantly reducing by-products and heat generation.
[0108] In summary, by comparing Comparative Examples 1-5 and Examples 1-15, it can be seen that after introducing appropriate amounts of FEC and acrylate compound monomers at the same time, the normal temperature / high temperature cycle performance, thickness expansion, safety performance and other aspects of the battery are significantly improved.
[0109] 2. Comparative Analysis of Examples 3, 16 to 29
[0110] By comparing Example 3 with Examples 16-21, it can be seen that after adding an appropriate amount of FEC and an appropriate amount of acrylate compound, when the same content such as 2% and different compositions of polynitrile compounds are added respectively, the normal temperature / high temperature cycle performance, thickness expansion, safety performance and other aspects of the battery are relatively good.
[0111] By comparing Example 3 with Examples 22-29, it can be seen that with an appropriate increase in the amount of the polynitrile compound, the thickness expansion rate of the battery can be better improved.
[0112] In summary, by adding appropriate amounts of FEC, acrylate compounds and polynitrile compounds to the electrolyte, the room temperature / high temperature cycle performance, floating gas production and safety performance of the battery are further improved. This is mainly due to the fact that the polynitrile additive can achieve very effective passivation of the high-voltage positive electrode, inhibiting the positive electrode interface side reactions, the rapid decay of the positive electrode structure, and the dissolution of transition metals.
[0113] 3. Comparative Analysis of Examples 21, 30 to 34
[0114] By comparing Example 21 with Examples 30-34, it can be seen that when the Si content in the negative electrode active material is gradually increased, FEC and acrylate compound monomers are appropriately increased. Although the increase in Si content leads to weakening of performance such as capacity retention rate and thickness expansion after cycling, after the coordinated use of acrylate compounds and FEC and the introduction of polynitrile compounds, the synergistic effect of FEC, semi-solid electrolyte and polynitrile compounds, on the one hand, strengthens the initial stability of the SEI film, and repairs the SEI film well during the cycle, inhibits the expansion of Si particles and its damage to the SEI film and the consumption of active lithium; on the other hand, it inhibits the positive electrode interface side reactions, the rapid decay of the positive electrode structure, and the dissolution of transition metals.
[0115] In summary, in high-silicon system batteries, not only higher energy density can be obtained, but also high-silicon content batteries can have better room temperature / high temperature cycle performance, thickness expansion, floating gas production and safety performance.
[0116] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0117] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present application may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and a condensed electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer arranged on the surface of the negative electrode current collector; wherein the negative electrode active material of the negative electrode material layer comprises a silicon-based material; The raw materials of the electrolyte include solvent, additive, lithium salt, monomer and initiator; wherein the additive includes fluoroethylene carbonate, and the monomer includes acrylate compound; The content of the silicon-based material in the negative electrode active material accounts for a% by mass, the content of the fluoroethylene carbonate in the electrolyte accounts for b% by mass, and the content of the acrylate compound in the electrolyte accounts for c% by mass, wherein b=a*0.5+9.5±m, c= a*0.3+0.7±n; Wherein, m is selected from 0 to 2; n is selected from 0 to 3; a>0, c>0; The mass ratio of the acrylic acid ester compound to the fluoroethylene carbonate is 0.029 to 0.589; The acrylate compound contains at least 2 acrylate groups or at least 2 methacrylate groups; The mass proportion of the monomer in the electrolyte is 1% to 10%; The silicon-based material is selected from at least one of SiO and SiC; The mass proportion of the silicon-based material in the negative electrode active material is 3% to 30%.
2. The lithium-ion battery according to claim 1, characterized in that: The mass proportion of the monomer in the electrolyte is 1% to 5%.
3. The lithium-ion battery according to claim 1, characterized in that The initiator is selected from at least one of an azo initiator or a peroxide; The content of the initiator is 1% to 5% of the mass of the monomer.
4. The lithium-ion battery according to claim 3, characterized in that: The initiator is selected from at least one of azobisisobutylnitrile initiator, azobisisoheptylnitrile, benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, diisopropyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, potassium sulfate, sodium persulfate, and ammonium persulfate.
5. The lithium-ion battery according to claim 1, characterized in that: The additive further comprises a polynitrile compound, wherein the polynitrile compound is selected from at least one of a dinitrile compound, a trinitrile compound, and a tetranitrile compound; The content of the polynitrile compound in the electrolyte is 1% to 10% by weight.
6. The lithium-ion battery according to claim 5, characterized in that: The polynitrile compound is selected from at least one of succinonitrile, glutaronitrile, adiponitrile, trans-butenedinitrile, trans-hexenedinitrile, 1,3,6-hexanetricarboxylic acid nitrile, ethylene glycol bis(propionitrile) ether, 1,3,4,6-hexanetetranitrile, 1,2,4,5-benzenetetranitrile, 2,3,5,6-pyrazinetetranitrile and ethertetranitrile.
7. The lithium ion battery according to any one of claims 1 to 6, characterized in that: The solvent is selected from at least two of ethylene carbonate, propylene carbonate, ethyl propionate, propyl propionate, ethyl methyl carbonate, diethyl carbonate, ethyl fluoroacetate, and dimethyl carbonate; and / or, The lithium salt is selected from at least one of LiPF6 and LiFSI, and the concentration of the lithium salt in the electrolyte is 0.8 mol / L~1.5 mol / L.
8. The lithium-ion battery according to claim 1, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on the surface of the positive electrode current collector, wherein the positive electrode material layer contains a positive electrode active material; wherein: The positive electrode active material is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, nickel cobalt aluminum, and lithium-rich manganese-based.
9. An electronic device, characterized in that: A lithium ion battery comprising the lithium ion battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
Gel polymer electrolyte power battery
CN106654353A
Electrolyte raw material composition, electrolyte, lithium ion secondary battery and preparation method thereof
CN111430780A
Lithium ion gel-state electrolyte, lithium ion battery and preparation method of lithium ion gel-state electrolyte
CN117477020A
Gel polymer electrolyte, semi-solid lithium ion battery and preparation method of semi-solid lithium ion battery
CN117810529A
Semi-solid electrolyte, preparation method thereof and electrochemical device
CN118712478A